PENGELOLAAN SITUS HOMIND PATIAYAM KUDUS JAWA TENGAH Nilai Penting dan Peran Para Pihak dalam pengelolaan Situs Berbasis Masyarakat - , Siswanto, Drs. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Patiayam site in Kudus Regency, Central Java is a Pleistocene site in northern Java. Vertebrata fossils often found by the local inhabitants make this site well-recognized. The findings attract lot of scientists to study the site, such as paleontologist, geologists, and archaeologists. ally after a fragment of human fossils categorized as Homo erectus were found there. To complete the data of the site as a hominid site in Java dated back to the Pleistocene, cultural data is crucial to be obtained. In 2007 remains of cultural activity were found in the form of scraper, hand-axe, and gigantolith made of silicified limestone and andesite. s, as well as developing the site. Parties involved include the government, As a site rich in reliccs of vertebrate fossils, history recorded prodigious fossil hunting or trading that took place since the colonial period. The continuously illegal fossil trading has caused a conflict of interest so that it becomes a threat to the preservation of the site. Since 2005, Patiayam site has attracted many interested stakeholders to carry out researches, preservation effort academics, observers, and community. Differences in understanding the site and lack of coordination among stakeholders resulted in the lack of progress in the management of the site and conflict of interest is likely to occur. The spirit of regional autonomy raises public and governmaent awareness for the management and conservation, but without clear and explicit management concept yet. identity The purpose of this study is to the effectiveness of government and societyâs role in preserving Patiayam site from threats. Through the identification of strength, weaknesses, oppportunities, and threats of this site will be submitted models or concepts on Patiayam site management, including research, conservation, and utilization or development.